2014
DOI: 10.1097/jom.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an e-Health Intervention Designed to Reduce Prolonged Occupational Sitting on Mean Arterial Pressure

Abstract: Objective:To evaluate the effect of a workplace health intervention designed to reduce prolonged occupational sitting on the mean arterial pressure (MAP) of desk-based employees.Methods:This randomized controlled trial involved an experimental group who received an e-health intervention and a control group who did not. The 13-week intervention passively prompted participants to stand and engage in short bouts of office-based physical activity by interrupting prolonged occupational sitting time periodically thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 41 publications
4
57
0
1
Order By: Relevance
“…This study also reported that participants could still recall the benefits of healthy lifestyle behaviours and contents of intervention sessions in detail at 24 months, suggesting that participants were aware of, and potentially still using, the behaviour change techniques and advice provided over the long term 35. The other, a 13-week computer software program to prompt reducing sedentary behaviour, resulted in a large (ES=0.67) reduction in mean arterial blood pressure (from 100.9±12 mm Hg to 90.6±11.5 mm Hg), compared with those not provided with this software (ES=0.01, from 102.0±10.6 mm Hg to 102.1±10.6 mm Hg) 42. Across the remaining multigroup studies with higher risk of bias ratings (in ≥7 items) the most commonly reported outcomes were fitness and weight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also reported that participants could still recall the benefits of healthy lifestyle behaviours and contents of intervention sessions in detail at 24 months, suggesting that participants were aware of, and potentially still using, the behaviour change techniques and advice provided over the long term 35. The other, a 13-week computer software program to prompt reducing sedentary behaviour, resulted in a large (ES=0.67) reduction in mean arterial blood pressure (from 100.9±12 mm Hg to 90.6±11.5 mm Hg), compared with those not provided with this software (ES=0.01, from 102.0±10.6 mm Hg to 102.1±10.6 mm Hg) 42. Across the remaining multigroup studies with higher risk of bias ratings (in ≥7 items) the most commonly reported outcomes were fitness and weight.…”
Section: Resultsmentioning
confidence: 99%
“…All but two multigroup studies (n=11) reported improvements in at least one outcome. The two studies with the lowest risk of bias found improvements in mean arterial blood pressure (large effect after 13 weeks) in a sedentary behaviour intervention42 and in healthy eating, sleep quality, stress and tobacco use (small effects 24 months after a 12-week programme) following peer-led wellness support 34 35. Details on findings from the remaining multigroup studies with higher risk of bias ratings can be found in the Results and table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the researchers' concern over self-selection, at a second participant meeting, only three (Mage = 44.00 ± 19.00 years) chose the active prompt condition, whereas eleven participants chose to be in the passive prompt condition (Mage = 47.18 ± 10.51 years). As researchers, we were aware of which condition had resulted in compliance in previous studies [3] [5] [6]; nonetheless, we were asked questions about the effectiveness of each condition. The researchers were all present and ensured that questions were answered neutrally as possible to further avoid contaminating the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Currently there is an emphasis in workplace health messages to decrease sitting time and increase incidental workday movement as a means of reducing sedentariness in the population. This emphasis is the result of a confluence of studies showing that prolonged bouts of sitting are a factor in the incidence of poor health outcomes [1], and that small periods of non-exercise physical activity (NEPA) offer health benefits [2] [3]. It has been suggested that sitting is a habit due to employees typically performing the majority of occupational tasks while desk-bound, in a repeated and consistent manner [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation